2016
DOI: 10.1097/nnr.0000000000000150
|View full text |Cite
|
Sign up to set email alerts
|

Drug Use and Multiple Sex Partners Among Homeless Ex-Offenders

Abstract: Background Transitioning into society after release from incarceration presents real challenges for male offenders; in California, up to 60% return to prison within three years following release. The risk for ongoing drug use and having sex with multiple sex partners is a significant challenge for ex-offenders preparing to enter the community. Objectives The aims are to describe drug use and sexual behavior (sex with multiple partners) prior to incarceration and six and 12 months following study enrollment u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
(57 reference statements)
1
4
0
Order By: Relevance
“…At the univariate level, the odds of engaging in unprotected sex were higher among participants who used illicit drugs such as cocaine and marijuana, which has been observed in previous research examining HIV risk behaviors post-incarceration (L. M. Adams et al, 2013; Nyamathi et al, 2016; Ricks et al, 2015; Zhu et al, 2015).…”
Section: Discussionsupporting
confidence: 69%
“…At the univariate level, the odds of engaging in unprotected sex were higher among participants who used illicit drugs such as cocaine and marijuana, which has been observed in previous research examining HIV risk behaviors post-incarceration (L. M. Adams et al, 2013; Nyamathi et al, 2016; Ricks et al, 2015; Zhu et al, 2015).…”
Section: Discussionsupporting
confidence: 69%
“…Participants were asked to report the number of people they had any kind of sex with in the past 12 months. Responses were dichotomized to 4 or more partners or fewer than 4 to align with the literature on multiple sexual partners and allow for comparisons with other studies and populations [ 7 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Other HIV risk behaviors such as having multiple sexual partners and concurrent sexual partners are prevalent among homeless populations, including ex-offenders and street-involved youth [ 15 , 16 ]. In a study of homeless men from Los Angeles [ 17 ], almost 40% reported multiple concurrent sex partners, i.e., having sex with more than one person around the same time, which is a known risk factor for HIV [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Developed nearly 25 years ago, the CHSCP model (Nyamathi, 1989) is based on the Lazarus Schema of Coping and Adaptation (Lazarus & Folkman, 1984) and the Schlotfeldt Health Seeking and Coping Paradigm (Schlotfeldt, 1981). The CHSCP has been well utilized by the authors for decades and has been tested with homeless populations who have participated in intervention programs designed to enhance HAV/HBV vaccination treatment compliance (Nyamathi et al, 2015), and reduce drug and alcohol use (Nyamathi, Zhang, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The CHSCP has been well-utilized by the authors for decades and has been tested with homeless populations who have participated in intervention programs designed to enhance hepatitis A and B virus vaccination treatment compliance (A. Nyamathi et al, 2015) and reduce drug and alcohol use (A. M. Nyamathi, Zhang, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%